The Relationship Between Complaint Handling To Patient Loyalty At Wonogiri Amal Sehat Hospital - Alfi Alifatul Maklufah; Achmad Djunawan (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2022)
The services that are considered lacking by some people will affect community dissatisfaction with hospital health services. Good complaint handling can change dissatisfied patients to satisfied or conversely. Complaints that are handled properly can build patient loyalty to the hospital. This study aimed to analyze the relationship between complaint handling and patient loyalty at Wonogiri Amal Sehat Hospital in 2022. This study used a quantitative method with a cross-sectional approach. This study has a total sample of 65 respondents. Complaint handling at the hospital in 2022 has 90.8% good category and 9.2% fair category, then patient loyalty at the hospital in 2022 has 73.8% high category and 26.2% medium category. The Spearman Rank Correlation coefficient value is 0.726 which is between 0.60-0.799. Between complaint handling and patient loyalty at the Wonogiri Amal Sehat Hospital has a strong relationship. As a suggestion, the hospital should improve the quality of the complaint handling speed.